Generation Smart Education Learning Process of Blockchain-Based in Universities - Hardjanto Nusantoro; Po Abas Sunarya; Nuke Puji Lestari Santoso; Sabda Maulana (Blockchain Frontier Technology, 2021)
Smart education in universities can be realized with a comprehensive use of IT infrastructure, various systems that are implemented to run this can take priority of the cloud computing and Internet of Things (IoT) and. Resulting in the need for connectivity into IoT gateways and nodes, as well as implementing an architecture that does not only rely on communication coverage via wireless, but needs to reduce energy consumption in order to save IoT node batteries to maximize performance. The use of such an architecture must prioritize blockchain technology that can provide security, accountability, and data transparency that can be managed by universities. This article discusses the key to early adoption of technology that can develop smart learning with smart learning. After the characteristics of the smart education or university are determined, then the details of the latest communication technologies that are most relevant to the smart education application can be analyzed. In addition, higher education requires learning about the use of blockchain. Therefore, this article will provide useful pointers in planning smart education development, as well as responsible and intelligent developers in the next generation.